Student's Chemical Bonds Concept: Rasch Model Analysis - Sri Mulyanti; Deni Ebit Nugroho; Lenni Khotimah Harahap (Universitas Islam Indonesia, 2023)
This study was conducted to measure students' conceptual understanding of chemical bonds. The test through an online form includes a two-level test—a total of 50 students who have studied chemical bonds as research subjects. The method used is quantitative through analysis with the dichotomous Rasch model. A total of seven sub-concepts of chemical bonds have been tested on students through a two-level test, namely questions, and reasons. The questions given were declared valid and reliable according to the Rasch model. The concept that is considered the most difficult for students is the description of orbitals and molecular hybridization